Lupus, vaccinations and COVID-19: What we know now. (September 2021) - Mason, Alice; Anver, Himashi; Lwin, May; Holroyd, Christopher; Faust, Saul N; Edwards, Christopher J
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the virus causing Coronavirus disease 2019 (COVID-19), has had a huge impact on health services, with a high mortality associated with complications including pneumonia and acute respiratory distress syndrome. Patients with systemic lupus erythematosus (SLE) are at increased risk of viral infections, and recent data suggests they may be at an increased risk of poor outcomes with COVID-19. This may be particularly true for those on rituximab or high dose steroids. A huge international effort from the scientific community has so far resulted in the temporary authorisation of three vaccines which offer protection against SARS-CoV-2, with over 30 other vaccines being evaluated in ongoing trials. Although there has historically been concern that vaccines may trigger disease flares of SLE, there is little convincing evidence to show this. In general lupus patients appear to gain good protection from vaccination, although there may be reduced efficacy in those with high disease activity or those on immunosuppressive therapies, such as rituximab or high dose steroids. Recent concerns have been raised regarding rare clotting events with the AstraZeneca/Oxford vaccine and it is currently unknown whether this risk is higher for those patients with secondary antiphospholipid syndrome. With the possibility of annual COVID vaccination programmes in the future, prospective data collection and registries looking at the effect of vaccination on SLE disease control, the incidence of COVID-19 in SLE patients and severity of COVID-19 disease course would all be useful. As mass vaccination programmes begin to roll out across the world, we assess the evidence of the use of vaccines in SLE patients and in particular vaccines targeting SARS-CoV-2.